2015
DOI: 10.1007/s12013-015-0693-6
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor β1 Promotes Migration and Invasion of Human Hepatocellular Carcinoma Cells Via Up-Regulation of Connective Tissue Growth Factor

Abstract: Hepatocellular carcinoma (HCC) is one of the most common malignant tumors with a poor patient survival. Expression of TGF-β1 is up-regulated in HCC and is thought to play a crucial role in the occurrence and development of HCC. However, the mechanism of TGF-β1-mediated facilitation of malignant growth and invasion remains unclear, although some previous studies highlighted a potential involvement of the connective tissue growth factor (CTGF). Here we demonstrate that the in vitro migration of the HCC cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…It was known that ACL had poor healing capacity, with a substantially high rate of failure (40–100%), even after surgical repair using suture (Strand et al, 2005, Taylor et al, 2015). The reconstruction of ACL has remained the gold standard of care for ACL injuries, especially for young individuals and some athletes who aim to return to high-level sporting activities (Liu et al, 2015a, Musahl et al, 2011). However, for now though, surgical treatment of ACL injury is costly, with variable outcomes (Wang et al, 2015, Kiapour et al, 2014), which are often not successful at returning patients to their pre-injury activity level (Ardern et al, 2011, Zaheer et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It was known that ACL had poor healing capacity, with a substantially high rate of failure (40–100%), even after surgical repair using suture (Strand et al, 2005, Taylor et al, 2015). The reconstruction of ACL has remained the gold standard of care for ACL injuries, especially for young individuals and some athletes who aim to return to high-level sporting activities (Liu et al, 2015a, Musahl et al, 2011). However, for now though, surgical treatment of ACL injury is costly, with variable outcomes (Wang et al, 2015, Kiapour et al, 2014), which are often not successful at returning patients to their pre-injury activity level (Ardern et al, 2011, Zaheer et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Liver histology revealed disrupted lobular architecture, bridging fibrosis, and necro-inflammatory liver damage. Liver fibrogenesis was confirmed by the increased deposition of collagen and the increased expression of α-Sma , a specific marker of hepatic stellate cell activation, 42 in addition to the upregulation of Tgf-β and Ctgf pro-fibrotic molecules 43, 44. The neoplastic nature of the hepatocellular nodules was confirmed by histology, which identified a spectrum of lesions ranging from dysplastic foci or nodules to HCC.…”
Section: Discussionmentioning
confidence: 96%
“…The evidences showed that the TGFβ1 participated in tumorigenesis, development and metastasis 30. The high level of TGFβ1 was associated with poor postoperative metastasis in colorectal cancer 31.…”
Section: Discussionmentioning
confidence: 99%